Saving Behavior of Thai Elderly - Tirapat, Sunti (NIDA Business Journal, 2025)
Demographic transitions have heightened the importance of understanding savings adequacy among the elderly as a key component of policy design to address population aging. In Thailand, where the elderly population is expanding rapidly amid middle-income status and fiscal constraints, this study investigates the economic and social determinants of savings adequacy for older individuals. Specifically, the analysis tests the role of financial literacy and cognitive ability in influencing adequate savings, while also examining the demand for asset management assistance. Utilizing survey data from 1,010 individuals aged 55 to 75 across representative provinces, the findings indicate that occupation, income, and health status are significant predictors of savings adequacy. Contrary to theoretical expectations, neither financial literacy nor cognitive ability exhibits a statistically significant association with adequate savings. Furthermore, demand for asset management assistance is primarily observed among elderly individuals with outstanding debt, while low income and limited social capital are not significant drivers of such demand. These results underscore the multifaceted nature of savings behavior among the elderly, shaped by economic, social, and health factors. The findings suggest that policy interventions aimed at enhancing retirement preparedness should adopt an integrated approach, as financial education alone may be insufficient to improve savings outcomes.